Dopamine‐Integrated Nanointerface between Fibrillar Matrix and Hydrophilic Nanohydroxyapatite Regulates Immune Microenvironment to Boost Endogenous Bone Regeneration. (17th January 2023) - Li, Xing; Li, Zhulian; Wang, Peilei; Lu, Gonggong; Tong, Lei; Liu, Quanying; Chen, Yafang; Lin, Jiangli; Luo, En; Liang, Jie; Jiang, Qing; Fan, Yujiang; et al.
Abstract: Driving endogenous bone regeneration by cell‐ and factor‐free biomaterials is the most ideal repair strategy. Herein, hybrid interleaved scaffold (HDSH) with nanosized interfacial integration is assembled by organic/inorganic interactive bonding at the nanoscale. With the help of transcriptome and proteome analysis, the regenerative mechanism of this scaffold is elaborated at the molecular level, which confirms that this strategy recreates a suitable immune microenvironment (anti‐inflammatory and M2‐polarizing) and drives functional cell and cytokine adhesion, as well as inchoate vascularization. It greatly enhances endogenous stem cell recruitment, and subsequently initiates robust vasculogenesis and osteogenesis. Significant bony reconstitution in the rabbit cranial defect model (Φ = 10 mm) is observed after 12 weeks, which realizes completely new bone coverage and 79% breaking load strength relative to the natural cranium. By enhancing nano‐sized functional interfacial integration, this strategy can provide effective guidance for developing highly bioactive bone‐regenerative implants. Abstract : Dopamine‐integrated nanointerface between fibrillar matrix and nHAp modulating M2 macrophage polarization and initiating endogenous stem cells recruitment to boost endogenous bone regeneration.